Synthesis and characterization of palladium (II) complex of Schiff base ligand: C-S bond cleavage and catalytic activity - Pattanayak, Poulami
Reaction of ligand, L-CH2Ph with Pd(CH3CN)(2)Cl-2 in acetonitrile in presence of PPh3 and subsequent addition of NaClO4 yielded Pd(II) complex, [Pd(L)(PPh3)](ClO4) 1 due to the S-C (CH2Ph) bond cleavage during complexation. Complex 1 was characterized by spectral analysis and the structure was authenticated by single crystal X-ray diffraction. The diffraction analysis revealed that the monoanionic ligand binds with palladium (II) in (N, N, S) fashion in a distorted square planar geometry where the fourth position is occupied by one tri phenyl phosphine group. One ClO4- ion satisfies the charge of the former aggregate, [Pd(L)(PPh3)](+). The complex [Pd(L)(PPh3)](ClO4), 1 exhibits a very good catalytic activity towards C-C bond formation. (C) 2015 Elsevier B.V. All rights reserved.